1995
DOI: 10.1093/humrep/10.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium increase and acrosome reaction in response to progesterone in human spermatozoa are correlated with in-vitro fertilization

Abstract: In this study we have investigated responsiveness to progesterone in spermatozoa from a group of unselected male partners of couples undergoing in-vitro fertilization (IVF). We evaluated progesterone-stimulated intracellular Ca [Ca 2+ ]j or acrosome reaction was observed in response to progesterone with the exception of one case. Our results indicate that [Ca 2+ ]| and acrosome reaction increases in response to progesterone can be of value in the prediction of sperm fertilizing ability. As the two paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 9 publications
7
73
2
Order By: Relevance
“…Isolation, sequencing, and further functional characterization of these two protein candidates of nongenomic P receptors are presently under investigation in our laboratory. As we have recently shown that a correlation exists between sperm responsiveness to P and sperm fertilizing ability (29,46), identification and characterization of nongenomic P receptor(s) may be clinically relevant not only in future research in male infertility, but also in the development of new contraceptive tools.…”
Section: Tablementioning
confidence: 99%
“…Isolation, sequencing, and further functional characterization of these two protein candidates of nongenomic P receptors are presently under investigation in our laboratory. As we have recently shown that a correlation exists between sperm responsiveness to P and sperm fertilizing ability (29,46), identification and characterization of nongenomic P receptor(s) may be clinically relevant not only in future research in male infertility, but also in the development of new contraceptive tools.…”
Section: Tablementioning
confidence: 99%
“…Spermatozoa were washed from seminal plasma and prepared by the swim-up procedure as described previously [16]. In some experiments, spermatozoa were separated on a Percoll gradient as described [5,17].…”
Section: Preparation Of Spermatozoamentioning
confidence: 99%
“…In humans, male factor infertility is highly correlated with failure of AR and/or the events that activate AR (1)(2)(3)(4). It is believed that the primary activator of AR in mammals is binding of the spermatozoon to the ZP (5), although AR can also be induced by progesterone (6 -8).…”
mentioning
confidence: 99%